Dinuclear Asymmetric Ruthenium Complexes with 5-Cyano-1,10-phenanthroline as a Bridging Ligand - Mellace, María G. (2004)
New dinuclear asymmetric ruthenium complexes of the type [(bpy)2Ru(5-CNphen)Ru(NH3)5] 4+/5+ (bpy ) 2,2′-bipyridine; 5-CNphen ) 5-cyano-1,10-phenanthroline) have been synthesized and characterized by spectroscopic, electrochemical, and photophysical techniques. The structure of the cation [(bpy)2Ru(5-CNphen)Ru(NH3)5] 4+ has been determined by X-ray diffraction. The mononuclear precursor [Ru(bpy)2(5-CNphen)]2+ has also been prepared and studied; while its properties as a photosensitizer are similar to those of [Ru(bpy)3] 2+, its luminescence at room temperature is quenched by a factor of 5 in the mixed-valent species [(bpy)2RuII(5-CNphen)RuIII(NH3)5] 5+, pointing to the occurrence of intramolecular electron-transfer processes that follow light excitation. From spectral data for the metal-to-metal charge-transfer transition RuII f RuIII in this latter complex, a slight electronic interaction (HAB ) 190 cm-1) is disclosed between both metallic centers through the bridging 5-CNphen.